Leadership initiatives and structure by the Church of Norway, within Norway, pertaining to HIV/AIDS - Elvik, Sasha-Monique (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.